Toxocara canis (Nematoda, Ascarididae): ultrastructure of the rachis and the ovarian wall - Brunanská, M (Folia parasitologica, 1994)
The oogonia and oocytes in the ovaries of Toxocara canis are joined to a cytoplasmic process called the rachis. The rachis is a much branched cytoplasmic mass without cell components in the germinal zone. At the end of the germinal zone and in the growth zone the cytoplasmic mass is formed into a central axial cylinder, containing small dense granules, lipid drops and glycogen. Throughout the growth zone shell granules similar to those present in the oocytes are also present in the rachis. Anterior to the opening of the ovaries into the oviduct the rachis disappears. The ovarian wall is composed of epithelial cells, adjoining the basal lamina. They are characterized by the presence of large numbers of mitochondria, especially in the germinal zone. The epithelial cells in the growth zone also contain rough endoplasmic reticulum, ribosomes and bundles of microfibrils. A dense tubular material occurs between the basal membrane of the epithelial cells and the basal lamina as well as in the wall intercellular spaces in the ovarian growth zone. Multivesicular labyrinth-like formations can also be observed in the epithelial intercellular spaces in the central portion of the T. canis ovary.
Keywords: Microscopy, Electron; Toxocara canis; Epithelium; psi; elektronová mikroskopie; Dogs; Oogonia; Oocytes; cytoplazma; ženské pohlaví; zvířata; oocyty; Basement Membrane; ovarium; epitel; Ovary; Cytoplasm; bazální membrána; oogonie; Female; Animals